Corneal hysteresis and its relevance to glaucoma. Issue 2 (March 2015) - Deol, Madhvi; Taylor, David A.; Radcliffe, Nathan M.
Abstract : Purpose of review: Glaucoma is a leading cause of irreversible blindness worldwide. It is estimated that roughly 60.5 million people had glaucoma in 2010 and that this number is increasing. Many patients continue to lose vision despite apparent disease control according to traditional risk factors. The purpose of this review is to discuss the recent findings with regard to corneal hysteresis, a variable that is thought to be associated with the risk and progression of glaucoma. Recent findings: Low corneal hysteresis is associated with optic nerve and visual field damage in glaucoma and the risk of structural and functional glaucoma progression. In addition, hysteresis may enhance intraocular pressure (IOP) interpretation: low corneal hysteresis is associated with a larger magnitude of IOP reduction following various glaucoma therapies. Corneal hysteresis is dynamic and may increase in eyes after IOP-lowering interventions are implemented. Summary: It is widely accepted that central corneal thickness is a predictive factor for the risk of glaucoma progression. Recent evidence shows that corneal hysteresis also provides valuable information for several aspects of glaucoma management. In fact, corneal hysteresis may be more strongly associated with glaucoma presence, risk of progression, and effectiveness of glaucoma treatments than central corneal thickness.